2021
DOI: 10.3389/fpsyg.2021.759351
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Diverse Exercise on Cognition and Mental Health of Children Aged 5–6 Years: A Controlled Trial

Abstract: The rate of learning and cognitive development is at its highest level in preschool-aged children, making this stage a critical period. Exercise has received increasing attention for its beneficial physical and mental health effects on the development of preschool children. This study investigated the effects of diverse exercise on the cognition of preschool children. Two classes were randomly selected from kindergarten classes of children aged 5–6 years, and designated as the experimental and control classes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…Such results may indicate that physical culture and physical exercises have a positive effect on some mental processes. This assumption is confirmed by the studies of many authors who have determined the positive dynamics of mental processes under the influence of the physical activity of schoolchildren [30,31,35,36].…”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…Such results may indicate that physical culture and physical exercises have a positive effect on some mental processes. This assumption is confirmed by the studies of many authors who have determined the positive dynamics of mental processes under the influence of the physical activity of schoolchildren [30,31,35,36].…”
Section: Resultsmentioning
confidence: 52%
“…A simple solution to a motor problem: how to move correctly, quickly, and accurately, how to correct a mistake -is a chain of mental operations, including observation, generalization, and decision-making. According to the authors, physical exercises not only increase the functional capabilities of the body, and the level of physical fitness of a person, but also help in the development of mental personality traits [30,31]. The hypothesis of the study is the assumption that the integration of prolonged running into the process of physical education at school in children aged 9-10 years will have a positive impact on the level of endurance development and a positive impact on the attention indicators of schoolchildren.…”
Section: Introductionmentioning
confidence: 99%
“…In addition previous studies have reported that doing sports promotes cognitive and emotional development, as well as increases cognitive performance, as children tend to be more motivated and self-controlled [ 9 , 47 , 48 ]. Nevertheless, BMI score is similar in both groups, BMI node is not linked with cognitive and motor domain in OPTIMAL-MVPA, representing “stability” of children who reach 300 min of recommended MVPA on weekdays.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, this unmanicured characteristic of the natural environments diversifies the actions a visitor can perform, often suppressed by the presumed notions of how to behave in a conventional, organized, safe, human-made setting such as most UNE. This diversity of affordances induces variability in body sub-system work, which has been connected to better health, cognitive functioning ( 40 , 41 ) and motor performance ( 42 , 43 ). Wellbeing is thus derived from the positive feelings of successfully engaging in action possibilities close to one's own capacities and skills, the right level of challenge ( 24 ), that is, that they themselves can change the environment and change their relation to its features ( 5 ).…”
Section: An Ecological Dynamics Approach To Physical Activity and Wel...mentioning
confidence: 99%